What is sexual about conflict-related sexual violence? Stories from men and women survivors - Dolan, Chris; Baaz, Maria Eriksson; Stern, Maria (International affairs (London), 2020)
Abstract Despite the prominent attention that the problem of conflict-related sexual violence (CRSV) has recently garnered globally, we still know far too little about what is sexual about sexual violence, according to whom, as well as why and how this matters in our efforts to prevent and redress its harms. A growing theoretical, political, legal and ethical imperative to ask questions about the sexual part of sexual violence across both war and peace is nonetheless emerging. This article therefore turns to the accounts of male and female survivors of CRSV at the at the Refugee Law Project (RLP) in Kampala, Uganda. In our reading of their accounts, we explore how the participants understand the possible imbrication of the perpetrator's sexual desire and pleasure with the violence they inflicted, as well as how they deem such intermeshing impossible or deeply problematic in and to the gendered frames that govern how they think about the distinctions between violence and sex, as well as themselves as sexual, social, embodied subjects. Read together, these conflicted and conflicting testimonies offer a vantage point from which to rethink some of the reductive truisms that persist in dominant policy-friendly accounts of wartime sexual violence—namely that such violence is about power and not about ‘sex’. The participants’ accounts thus urge us, as scholars and policy advocates, to resist reducing the multi-layered experiences of victim/survivors of sexual violence to fit into the palatable narratives of victimhood that prevail in humanitarian, juridical and policy spaces.